Training perceptions, engagement, and performance: comparing work engagement and personal role engagement. Issue 1 (1st January 2016) - Fletcher, Luke
Abstract : The purpose of this study was to compare two engagement constructs (work engagement and personal role engagement) with regard to their relationship with training perceptions and work role performance behaviours. It was hypothesised that personal role engagement would show incremental validity above that of work engagement at predicting work role performance behaviours and be a stronger mediator of the relationships between training perceptions and such behaviours. Questionnaire data were gathered from 304 full-time working adults in the UK. As predicted, personal role engagement was found to explain additional variance above that of work engagement for task proficiency, task adaptability, and task proactivity behaviours. Moreover, personal role engagement was a stronger mediator of the relationship between training perceptions and task proficiency as well as between training perceptions and task adaptability. Both work engagement and personal role engagement mediated the relationship between training perceptions and task proactivity to a similar degree. The findings suggest that personal role engagement has better practical utility to the human resource development domain than work engagement and indicates that future research may benefit from adopting the personal role engagement construct.